1999
DOI: 10.1007/pl00004009
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Caffeine, Fluid Intake and Urinary Incontinence in Older Rural Women

Abstract: Forty-one women completed the first phase (self-monitoring) of the Behavioral Management for Continence (BMC) intervention, while working with a nurse during home visits to reduce involuntary urine loss as part of the parent study involving older, rural women living at home. A decrease in dietary caffeine intake and an increase in fluid intake were most frequently recommended. The relationship between a decrease in the amount of dietary caffeine consumed and fewer daytime episodes of involuntary urine loss app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
1
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(64 citation statements)
references
References 17 publications
0
60
1
3
Order By: Relevance
“…However, in a case -control study, the mean intake of coffee was significantly higher in women with detrusor instability than in controls 13 and an increase in detrusor pressure after administration of caffeine has been shown experimentally 14 . An association between a decrease in amount of dietary caffeine consumed and fewer daytime episodes of incontinence was found in an intervention study, although it was not statistically significant 15 .…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…However, in a case -control study, the mean intake of coffee was significantly higher in women with detrusor instability than in controls 13 and an increase in detrusor pressure after administration of caffeine has been shown experimentally 14 . An association between a decrease in amount of dietary caffeine consumed and fewer daytime episodes of incontinence was found in an intervention study, although it was not statistically significant 15 .…”
Section: Introductionmentioning
confidence: 80%
“…The severity index has been validated against a 48 hour 'pad weighing' test 21,22 . According to this test, slight incontinence means a leakage of 6 g/24 hours (95% CI 2 -9), moderate incontinence means a leakage of 17 g/24 hours (95% CI [13][14][15][16][17][18][19][20][21][22] and severe incontinence means a leakage of 56 g/24 hours (95% CI 44 -67).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, 41 patients' daily cafeinated beverages consumption was reduced from 829 ± 385 to 489 ± 312 ml in 4 weeks. As a result, their daily urinary leakage and UI episode were decreased from 42.21 ± 77.34 to 24.09 ± 40.93 and from 2.60 ± 2.65 to 1.68 ± 1.52, respectively [8]. By contrast, outcomes from a prospective randomized trial showed that reduced cafeine intake could only improve patients' symptoms of frequency and urgency signiicantly, but had no efect on reduction of urinary leakage [9].…”
Section: Dietary Modiicationsmentioning
confidence: 95%
“…They found that luid intake restriction could decrease the episode of both UUI and SUI signiicantly [15]. Another study, however, showed that increased luid intake was not related to episode of UI; even an increased urine volume was observed [8]. Hashim et al further explored the relationship between luid intake restriction and LUTS in patients with overactive bladder (OAB).…”
Section: Dietary Modiicationsmentioning
confidence: 99%
“…Özellikle taze sıkılmış meyve suları, süt, ayran ve çorbalar hem uygun sıvı kaynakları olması hem de diğer besin öğelerini de içermeleri açısından tercih edilebilir. Kafein içeren (kahve, çay, kola gibi) içecekler idrar çıkışında artmaya neden olarak sıvı gereksinmesini artmasına sebep olabileceğinden çok sık tercih edilmemelidir (55,56).…”
Section: Sıvı Alımıunclassified